2009
DOI: 10.3858/emm.2009.41.12.095
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 4-1BB and 4-1BBL in thymocytes during thymus regeneration

Abstract: CD8+ DP and the intermediate thymocytes during thymus regeneration. RT-PCR and Western blot analyses confirmed the presence and elevated levels of 4-1BB and 4-1BBL mRNA and protein in thymocytes during thymus regeneration. We also found that the interaction of 4-1BB with 4-1BBL promoted thymocyte adhesion to thymic epithelial cells. Our results suggest that 4-1BB and 4-1BBL participate in T lymphopoiesis associated with positive selection during recovery from acute thymic involution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The mice were allowed to acclimate to their environment for 1 week, and were used at 8-10-weeks-of-age. Because cyclophosphamide, a DNA alkylating agent commonly used in chemotherapy, is a long-established method for investigating thymic regeneration [ 23 - 28 ], the animals were given a single intraperitoneal dose of cyclophosphamide (400 mg/kg body weight, Sigma, St. Louis, MO, USA) in normal saline and were killed in groups of four or more at 3, 7, and 14 days after injection. Mice given the same volume of normal saline were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…The mice were allowed to acclimate to their environment for 1 week, and were used at 8-10-weeks-of-age. Because cyclophosphamide, a DNA alkylating agent commonly used in chemotherapy, is a long-established method for investigating thymic regeneration [ 23 - 28 ], the animals were given a single intraperitoneal dose of cyclophosphamide (400 mg/kg body weight, Sigma, St. Louis, MO, USA) in normal saline and were killed in groups of four or more at 3, 7, and 14 days after injection. Mice given the same volume of normal saline were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…4-1BB is expressed on a multitude of cells of the hematopoietic lineage ( 13 ). While 4-1BB is widely known to be transiently upregulated on CD8 T cells following activation ( 14 18 ), 4-1BB can also be expressed on activated CD4 helper T cells ( 17 , 19 , 20 ), B cells ( 21 , 22 ), regulatory T cells ( 23 ), natural killer (NK) cells ( 24 26 ), natural killer T (NKT) cells ( 27 ), gamma-delta T cells ( 28 ), dendritic cells ( 29 , 30 ), mast cells ( 31 ), osteoclasts ( 32 , 33 ), thymocytes ( 34 ), early myeloid progenitor cells ( 35 , 36 ), and activated endothelium ( 37 40 ). Human neural cells also express 4-1BB, including neurons, astroglia, and microglia in the brain ( 41 ).…”
Section: The Role Of 4-1bb In the Immune Responsementioning
confidence: 99%
“…The strategies developed thus far; such as the use of sex steroid ablation (Greenstein et al, ; Windmill and Lee, ), keratinocyte growth factor (Min et al, ; Alpdogan et al, ; Rossi et al, ), IL‐7 (Bolotin et al, ; Mackall et al, ; Aspinall et al, ; Goldberg et al, ), and in vitro‐generated progenitor T‐cells (Awong et al, ), could effectively restore the thymic architecture and cellularity in animal models. In addition, in previous studies, we showed that other factors such as nerve growth factor (Lee et al, , ), 4‐1BBL (Kim et al, ), receptor activator of nuclear factor‐κB ligand (Lee et al, , ), and TrkA neurotrophin receptor (Yoon et al, ) appear to be important in thymic regeneration. We used stem cell‐based gene therapy to enhance T‐cell reconstitution, and demonstrated the stimulatory effect of HGF‐hATMSCs on thymic regeneration for promoting TEC proliferation and IL‐7 expression in vitro, as well as to increase of the thymus size and the number of thymocytes in a rat model of CY‐induced acute thymus involution.…”
Section: Discussionmentioning
confidence: 65%